The effectiveness of training routine with reference to the physiological demand of squash match play - Majumdar, P.; Mandal, M.; Yadav, D. (International Journal of Applied Sports Sciences, 2009)
The present study was taken up to monitor the physiological demands of squash play based on heart rate and lactate response while in a competitive situation. Four on court specific training programs were evaluated based on lactate response and performance time to find out their effectiveness with the actual demands of the game. Method: 33 male and 9 female junior squash players volunteered for this study. Body fat was calculated indirectly from skin fold thickness a using Harpenden skin fold caliper at four sites: biceps, triceps, sub scapular and supra iliac. Body fat was calculated from body density. The cardio respiratory variables (VO2 max) at maximal effort were determined during a graded protocol of running on a treadmill starting from 8 Km/hr and increasing every 2 min. at the rate of 2 km/hr till volitional exhaustion. The expired air sample was analyzed by Gas Analyzer (Oxycon Champion- Germany). Four on court drills were monitored and lactate level and timing/court coverage were registered. For estimating whole blood lactate, capillary blood samples were drawn from a finger tip between 2 min and 3 min. after the cessation of the activity. The samples were analyzed in a calibrated automatic lactate analyzer in order to estimate whole blood lactate. The data were subjected to statistical treatment such as mean and standard deviation. One-way ANOVA were computed to assess the difference in heart rate and lactate among the three games. Result: Repeated measures of ANOVA demonstrated no significance difference observed in gender in terms of heart rate and lactate response during three games. The heart rate response in males ranged from 157-177, 162-182 and 165-182 beats. min-1 for games 1, 2 and 3 respectively. In females, the heart rate response in 3 games revealed 156-181, 165-183 and 163-181 beats. min-1. Peak game lactate found for males and females were 4.10 and 4.14 mM.l-1 achieved after the third and second game respectively. Estimated peak lactate in four on court drills i.e. ghosting, court run, agility and box sprints were 10.66±3.07, 14.00±1.79, 16.90±2.80 and 13.11±2.40 for males and 12.251.79, 13.78±2.17, 17.30±2.53 and 13.46±4.37 mM.l-1 for females respectively. Conclusion: In all the on court drills, the level of blood lactate was much higher than game lactate. The higher lactate levels cause metabolic acidosis and therefore may not prove to be an effective training routine unless modified in terms of duration/ intensity to optimize training benefit.